Urgensi Etika Islam dalam Kegiatan Bisnis - Prastika, Yurika; Sukti, Surya (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Business ethics is the behavior of entrepreneurs in running their businesses. In general, business ethics can create a good working environment in such a way that it does not cause conflict between entrepreneurs and the companies they manage. This study uses a qualitative descriptive approach that will explain the urgency of ethics in economic and business activities. This study also uses the library research method, in addition to efforts to use library research in this study through a review of scientific works, in the form of articles published in journals, and the like. The results of the study found that human nature influences ethical values ​​where the pure human nature and tends towards truth is an important foundation in developing ethics. Islamic economics in it the value of monotheism is the basis of ethics for someone who runs a business or other muamalah activities and ethics is the foundation for an entrepreneur in running his business. If a Muslim runs his business, then the blessings from the results of his business are what guarantee the sustainability of his business.